PSYCHOLOGICAL CONTRACT AND ITS IMPLICATIONS ON FACULTY RETENTION IN HIGHER EDUCATION SECTOR OF PUNJAB - Kaur, Jasleen (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the influence of psychological contract dimensions on employee retention in higher education institutions, focusing on both public and private sector organizations in Punjab. Using a structured questionnaire and a sample of 473 full-time academic staff, exploratory factor analysis (EFA) identified five key dimensions of the psychological contract: transactional, training and development, relational, balanced, and socio-emotional fulfillment. Structural equation modeling (SEM) was applied to assess the impact of each dimension on employee retention. The results revealed that training and development, relational, transactional, and balanced contracts significantly and positively influence retention, with training and development emerging as the most influential. However, socio-emotional fulfillment did not have a significant impact. The study highlights the importance of aligning organizational practices with employee expectations to foster long-term commitment. These findings offer practical implications for human resource strategies aimed at improving retention and contribute to the theoretical understanding of psychological contracts in academic settings.